Walki armii rzymskiej z koczownikami w Afryce za czasów pierwszej tetrarchii (próba rekonstrukcji wydarzeń) - Wełna, Kamil (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
This article aims to reconstruct events that took place in the years 289–293 AD and 297–299 AD in the African provinces of the Roman Empire. This refers to the battles that Emperor Maximian and earlier governors of these provinces waged with the coalition of Berber tribes known in the sources as the Quinquegentanei (five tribes). For the first time in Polish scientific literature this paper tries to reconstruct the chronology and evaluate the events themselves.